STRATEGI BERTAHAN HIDUP KOMUNITAS MISKIN DI KAMPUNG KRAMAT SENEN JAKARTA PUSAT - Rustanto, Bambang (Sekolah Tinggi Kesejahteraan Sosial (STKS) Bandung, 2016)
Abstract The background of this research is the fact of life of poor communities in urban areas should be supported by the carrying capacity of the environment. The Population density and settlements can reduce the ability of the environment to grow well. To maintain the life of poor communities required maintenance of village environment. Socio-liabilities community is measured by peace and social cohesion of the daily life of its citizens.This research uses qualitative research methods with fenomologis study models to see specific picture of social change in poor communities in urban areas. While the data collection tools by using in depth interviews with the support of participant observation and documentation study. Informants involved, among others, the local organization committee, local government officials such as RT/RW, as well as community leaders and other supporters informants from poor communities themselves.The results of this research found that differences in ethnic and regional origins does not cause difficulty in tolerating but trouble occurs in the event of differences of religion and belief. The social life of the community can be distracted and not run stable if one member or several people perform actions that asocial with troublemakers in the village. This is due to social phobia in the community from one group to another group. The conclusion of this research that there is the role of leaders and informal leaders or formal leaders as controlling social life of its citizens, has a duty to maintain social harmony or Latent Maintenance of this, so that the community was able to sustain life even in conditions of poverty and live in slums. Key words: poor communities, urban poverty and social workAbstrakLatar belakang penelitian ini adalah kehidupan komunitas miskin perkotaan yang harus ditunjang dengan daya dukung lingkungan hidupnya. Kepadatan pendudukan dan permukiman dapat menurunkan kemampuan lingkungan hidup untuk berkembang secara baik. Untuk mempertahankan hidup komunitas miskin diperlukan pemeliharaan lingkungan kampungnya. Sosialiabilitas komunitas diukur oleh kedamaian dan kerukunan sosial dari kehidupan sehari-hari warganya.Penelitian ini menggunakan metode penelitian kualitatif dengan studi fenomenologis untuk melihat secara khusus gambaran perubahan sosial pada komunitas miskin di perkotaan. Teknik pengumpulan data menggunakan wawancara mendalam dan didukung oleh obeservasi partisipasi dan studi dokumentasi sedangkan informan terdiri dari warga setempat, tokoh masyarakat, pengurus RT/RW dan pengurus organisasi sosial lainnya. Hasil penelitian ini menemukan bahwa perbedaan suku dan asal daerah tidak menimbulkan kesulitan dalam bertoleransi tetapi kesulitan terjadi apabila terjadi perbedaan agama dan keyakinan. Kehidupan sosial komunitas dapat terganggu dan tidak berjalan stabil apabila salah satu anggota atau beberapa orang melakukan tindakan yang asosial dengan membuat keornaran dalam kampung. Hal ini disebabkan adanya social phobia dalam komunitas dari golongan satu terhadap golongan lainnnya.Kesimpulannya disini peran para tokoh dan pemimpin informal maupun formal selaku pengendali kehidupan sosial warganya, mempunyai tugas untuk menjaga kerukunan sosial atau laten maintanance ini, sehingga komunitas itu mampu mempertahankan kehidupannya meskipun dalam kondisi kemiskinan dan tinggal di daerah kumuh.Kata kunci: komunitas miskin, kemiskinan kota dan Pekerjaan Sosial